EFFICACY OFINFLIXIMABIN THE TREATMENTOF CROHN’S DISEASEIN CHILDREN - E. G. Tsimbalova; A. S. Potapov; M. M. Venedictova; F. F. Shavrov (Вопросы современной педиатрии)
This paper shows the research results of the biological therapy with chimeric monoclonal antibody to tumor necrosis factor (TNF) (infliximab). 33 children aged 6 to 18 years with various forms of Crohn’s disease were enrolled in the study. Therapy duration ranged from 3 months to 1 year or more. After the induction course of therapy efficacy was 94%, clinical remission was achieved in 70% of patients, after 1 year of therapy efficacy of therapy was reduced to 84%, clinical remission was observed in 70% of children. Endoscopic remission rate after induction was observed in 24% of children, and in 29% after 54 weeks of therapy. After one year of treatment in 9 out of 11 children glucocorticoid therapy was completely stopped. Adverse events after infliximab administration were observed in 9% of children. One child was withdrawn from the study due to infliximab intolerance.